2005
DOI: 10.1021/jp0551521
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Colloidal Hard Tetragonal Parallelepipeds (Cuboids):  A Monte Carlo Simulation Study

Abstract: The impact of particle geometry on the phase behavior of hard colloidal tetragonal parallelepipeds (TPs) was studied by using Monte Carlo simulations in continuum space. TPs or "cuboids" of aspect ratios varying from 0.25 to 8 were simulated by approximating their shapes with multisite objects, i.e., via rigid clusters of hard spheres. Using equation of state curves, order parameters, radial distribution functions, particle distribution functions along three directions, and visual analysis of configurations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 33 publications
6
74
1
3
Order By: Relevance
“…In contrast to earlier conjectures [11][12][13] , we now find clear evidence of layering in the cubatic phase (also observed in [32]) which becomes visible in our redefined particle distribution functions (see details in SI). While the finite size of our system prevents us from ascertaining the range of such a positional order, the appreciable D values observed at these densities indicates that the system has liquid-like behaviour and there is sufficient translational disorder for layers to rearrange dynamically.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to earlier conjectures [11][12][13] , we now find clear evidence of layering in the cubatic phase (also observed in [32]) which becomes visible in our redefined particle distribution functions (see details in SI). While the finite size of our system prevents us from ascertaining the range of such a positional order, the appreciable D values observed at these densities indicates that the system has liquid-like behaviour and there is sufficient translational disorder for layers to rearrange dynamically.…”
contrasting
confidence: 99%
“…These ordered assemblies have distinctive electronic, optical, and dynamical properties 4,5 and are highly desirable for fabrication of advanced electronic, photonic, and rheological devices 6,7 . Although numerous theoretical [8][9][10][11][12][13] and experimental 14,15 studies on mesophase behaviour of particles with anisotropic shapes have been reported, a roadmap marking out the most probable mesophases that could be formed by constituent particles with particular geometrical features is still incomplete. Exploring such relations will translate into a deeper understanding of the phase behaviour of colloidal systems with different particle shapes; e.g., Jiao et al 16 reported that unlike ellipsoids, convex superballs can be optimally packed in dense Bravais lattices because they are less symmetric but more isotropic than the former.…”
mentioning
confidence: 99%
“…The hard sphere system [8,9], which provided a good insight into physics underlying the freezing of rare gases [10,11], is probably the most widely known example. Monte Carlo (MC) simulations of anisotropic hard-body systems have shown that they are able to mimic various liquid-crystalline and solid phases [12][13][14][15][16][17][18][19][20][21][22]. In particular, it was shown [23][24][25][26] that a crude model of a diatomic molecule, the hard homonuclear dumbbell -formed by two fused spheres, each of diameter r, with centers separated by distance d -can form the above-mentioned rotator phase besides the fluid and the fully-ordered crystalline phases.…”
Section: Introductionmentioning
confidence: 99%
“…53 The more general algorithms for detecting the overlap of two orthorhombic boxes are then simplified to the case of cubes with edge d, following the same approach used for simple hard cubes. 47,54 An alternative approach to modelling a polyhedron as a single object is by fusing repulsive spheres into a rigid body. Such models were used in early simulations of colloidal cubes, 55 although the slight corrugations of the cube surfaces introduced some noticeable artefacts.…”
Section: Modelmentioning
confidence: 99%